Mudharabah Contracts at KJKS BMT UGT Sidogiri: Implementation and Analysis of the Compilation of Sharia Economic Laws - Hafid, Hafid; Maulana, Diky Faqih (Sharia and Law Faculty of Sunan Kalijaga Islamic State University Yogyakarta, 2023)
Abstract: The research is motivated by the practice of Mudharabah contracts at KJKS BMT UGT Sidogiri Branch Sidodadi Surabaya, where the implementation of the offer and acceptance (ijab qabul) terms in Mudharabah contracts for opening Shariah Savings Accounts does not align with the guidelines set by the central KJKS BMT UGT Sidogiri. The purpose of this research is to examine the implementation of Mudharabah contracts in Shariah Savings Accounts at KJKS BMT UGT Sidogiri Branch Sidodadi Surabaya and to understand the implementation of Mudharabah contracts in Shariah Savings Accounts at KJKS BMT UGT Sidogiri Branch Sidodadi Surabaya from the perspective of Islamic Economic Jurisprudence (KHES). The research method used in this study is qualitative research. This research falls under the category of field research. Data collection was conducted through observation techniques, interviews, documentation, and purposive sampling to address the issues in the field. Data analysis was performed using qualitative descriptive analysis techniques. The findings of this research reveal several key points. Firstly, the procedure for opening Shariah Savings Accounts at KJKS BMT UGT Sidogiri Branch Sidodadi complies with the regulations of KJKS BMT UGT Sidogiri Central. However, during the implementation of the Akad Shigat, it is expressed with the terms of a trust (wadi'ah) contract, which is not in accordance with the procedure for Mudharabah contracts. Secondly, the officials still use the terms of a trust (wadi'ah) contract during the Akad Shigat, while the instructions from KJKS BMT UGT Sidogiri Central state that all savings products should use the terms of a Mudharabah contract. According to KHES, as stipulated in Article 49, Paragraphs 1 and 2, there is no allowance for alternative interpretations in the contract interpretation. Abstrak: Penelitian dilatarbelakangi oleh adanya praktek akad mudharabah di KJKS BMT UGT Sidogiri Cabang Sidodadi Surabaya dimana pelaksanaan shighat ijab qabul akad mudharabah pada pembukaan Tabungan Umum Syariah menggunakan akad titipan yang tidak sesuai dengan juknis dari KJKS BMT UGT Sidogiri Pusat. Tujuan penelitian ini adalah mengetahui implementasi akad Mudharabah pada Tabungan Umum Syariah di KJKS BMT UGT Sidogiri Cabang Sidodadi Surabaya dan mengetahui implementasi akad Mudharabah pada Tabungan Umum Syariah di KJKS BMT UGT Sidogiri Cabang Sidodadi Surabaya dalam perspektif KHES. Metode Penelitian yang digunakan adalah metode penelitian kualitatif. Jenis penelitian ini menggunakan jenis penelitian lapangan (field research). Pengumpulan data dilakukan melalui teknik observasi, Interview/ wawancara, dokumentasi dan purposive sampling guna menjawab permasalahan yang ada di lapangan. Sedangkan analisa data menggunakan teknik analisa deskriptif kualitatif. Hasil dari penelitian ini menghasilkan beberapa temuan. Pertama, prosedur pembukaan buku Tabungan Umum Syariah di KJKS BMT UGT Sidogiri Cabang Sidodadi sesuai dengan ketentuan KJKS BMT UGT Sidogiri Pusat. Namun, ketika pelaksanaan Shigat Akad, diucapkan dengan sighat akad titipan (wadi’ah) tidak sesuai dengan prosedur akad mudharabah. Kedua, pelaksanaan sighat akad petugas masih menggunakan sighat akad titipan (wadi’ah), sedangkan instruksi dari KJKS BMT UGT Sidogiri Pusat, seluruh produk tabungan menggunakan sighat akad mudharabah. Berdasarkan KHES pada pasal 49 Ayat 1 dan 2 tersebut tidak diperbolehkan adanya interpretasi lain dalam penafsiran akad.